Implementation of the Cooperative Integrated Reading and Composition Model in Improving Elementary School Students' Reading Comprehension Skills - Wandrianie Imandah Lilyandine; Ilyas Idris; Ika Aryastuti Hasanah; Tabroni Tabroni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the impact of the Cooperative Integrated Reading and Composition (CIRC) learning model on the ability of fourth-grade students of SD Negeri 28/IV in Jambi to understand Indonesian language materials, particularly in identifying main ideas, supporting arguments, and summarizing the reading content. A quantitative method and a quasi-experimental design with a non-equivalent control group were used. The study sample consisted of 56 students, categorized into an experimental group and a control group. Data were collected through pre-tests and post-tests, and analyzed using normality tests, assessment of homogeneity of variance, and t-tests. The results showed that the pre-test score of the experimental group was 53.93, which increased to 87.50 in the post-test; the score of the control group increased from 54.29 to 71.79. Hypothesis testing revealed a significant difference in student performance before and after the implementation of the CIRC model. This indicates that the CIRC model surpasses conventional learning methods in improving students' reading ability. This study used a quasi-experimental design to implement the CIRC model in reading materials for fourth-grade students at SD Negeri 28/IV in Jambi, focusing on the main idea and supporting arguments of the text. This study conducted a comparative analysis between the experimental group and the control group in a real elementary school learning environment.